Healthcare Workers during the COVID-19 Pandemic from a Street-Level Bureaucracy Perspective - A Narrative Review of Literature (Universitas Medica, 2021)
Street - level bureaucrats are professionals whose main role consists in the implementation of public policies at a community level, guiding themselves through the use of autonomy and discretion.. In this narrative review of literature 44 articles that had information about street level bureaucracy regarding healthcare workers in the covid 19 pandemic in specific countries (China, United States, Italy, Brazil, Mexico and Colombia) were selected from various databases and analyzed to explore how the implementation of health public policies during the current COVID - 19 outbreak impacted and shaped the work of healthcare workers. Various ideas were extracted and analyzed using the street level bureaucracy model as a reference point. We concluded that street level bureaucrats have played a crucial role in this pandemic and that providing them with government support, clear public policies and enough resources is essential for them to correctly manage public health problems. Further research needs to be done regarding the consequences brought upon street level bureaucrats by the pandemic and the impact that street level bureaucrats have had in countries like Colombia.